2015
DOI: 10.1016/j.neuron.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Visual Areas Exert Feedforward and Feedback Influences through Distinct Frequency Channels

Abstract: Visual cortical areas subserve cognitive functions by interacting in both feedforward and feedback directions. While feedforward influences convey sensory signals, feedback influences modulate feedforward signaling according to the current behavioral context. We investigated whether these interareal influences are subserved differentially by rhythmic synchronization. We correlated frequency-specific directed influences among 28 pairs of visual areas with anatomical metrics of the feedforward or feedback charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

145
1,120
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,178 publications
(1,274 citation statements)
references
References 50 publications
145
1,120
9
Order By: Relevance
“…Overall, these findings highlight the role of the beta-band frequency channel in predictive processing: beta effects have been observed both in the domain of local power modulations (poststimulus beta power increase, as in Arnal et al, 2011) and in the analysis of larger-scale brain connectivity (increase pre-stimulus beta connectivity, as in Bastos et al, 2015). However, if the internal forward models employed in language production are involved also in language prediction we should observe pre-stimulus beta power desynchronization during language comprehension (see also pre-stimulus beta synchronization associated to predictive timing, Arnal et al, 2014).…”
Section: Oscillatory Dynamics Reflecting Pre-stimulus Predictionmentioning
confidence: 71%
See 3 more Smart Citations
“…Overall, these findings highlight the role of the beta-band frequency channel in predictive processing: beta effects have been observed both in the domain of local power modulations (poststimulus beta power increase, as in Arnal et al, 2011) and in the analysis of larger-scale brain connectivity (increase pre-stimulus beta connectivity, as in Bastos et al, 2015). However, if the internal forward models employed in language production are involved also in language prediction we should observe pre-stimulus beta power desynchronization during language comprehension (see also pre-stimulus beta synchronization associated to predictive timing, Arnal et al, 2014).…”
Section: Oscillatory Dynamics Reflecting Pre-stimulus Predictionmentioning
confidence: 71%
“…Bastos et al (2015) analyzed the oscillatory dynamics of the primate visual system employing electrocorticography recordings from grids implanted along the whole visual system of monkeys. They observed that increased coherence in the beta band was associated with feedback influences from higher processing regions to primary visual regions.…”
Section: Oscillatory Dynamics Reflecting Pre-stimulus Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is of particular relevance to feedback modulation because it has been shown that across many different cortical regions feedforward signalling involves synchronization at gamma frequencies and that feedback modulates feedforward signalling via synchronization at beta frequencies (Bastos et al, 2015).…”
Section: Overview Of the Neurobiological Evidencementioning
confidence: 99%